A high energy density full lithium-ion cell based on specially matched coulombic efficiency. Issue 11 (24th February 2016) - Zou, Bangkun; Hu, Qiao; Qu, Danqi; Yu, Ran; Zhou, Yuting; Tang, Zhongfeng; Chen, Chunhua
Abstract : Li-rich cathodes and Mn x Co1− x O anodes are selected to construct a full-cell by specially matched coulombic efficiency, which delivers particularly high energy density. Abstract : Nano-spherical Li-rich cathodes and Mn x Co1− x O anodes are synthesized from as-solvothermal Mn x Co1− x CO3 ( x = 1, 0.8, and 0.5) precursors. Based on the half-cell studies of these materials, Li-rich 0.5Li2 MnO3 ·0.5LiMn0.5 Ni0.5 O2 with a high reversible capacity of 247 mA h g −1 and binary transition metal oxide Mn0.8 Co0.2 O with a reversible capacity of 759 mA h g −1 are selected respectively as the optimal positive and negative electrodes to construct a full cell. Such an electrode match-up, i.e. Li-rich/Mn0.8 Co0.2 O full cell ("N-cell"), allows no need for pre-activation of the metal oxide anode. This "N-cell" can deliver a high reversible capacity of 205 mA h g −1 and particularly rather high volumetric energy density, which is about 31% higher than that of a Li-rich/graphite full cell ("T-cell"). The special coulombic efficiency match-up and tailored microstructures and compositions of the electrode materials are all crucial to achieve such a high energy density.